Effect of Nylon Wick Technique on Early Intraocular Pressure Control in Nonvalved Aqueous Shunt Surgery. Issue 1 (January 2021) - Swaminathan, Swarup S.; Quist, Michael S.; Dawson, Lindsay E.; Rothman, Adam L.; Herndon, Leon W.
Abstract : Precis: The use of nylon wicks with fenestrations in nonvalved aqueous shunt surgery significantly reduces intraocular pressure (IOP) and glaucoma medication usage in the immediate postoperative period compared with the use of fenestrations alone. Purpose: To compare early postoperative IOP and medication usage in patients undergoing implantation of a nonvalved aqueous shunt device with fenestrations only or fenestrations with nylon wicks. Methods: A retrospective review of all nonvalved aqueous shunt insertions completed by one surgeon (L.W.H.) was completed using current procedure terminology. Patients undergoing Baerveldt or ClearPath 350 mm 2 aqueous shunt insertion with fenestrations only (n=37) or fenestrations with 2 nylon wicks were identified (n=92). All devices were ligated with 7-0 Vicryl (polyglactin) suture, and either 4 fenestrations or 2 fenestrations and two 9-0 nylon wicks were placed anterior to the ligature. Data regarding visual acuity (VA), IOP, number of glaucoma medications, and complications were collected from the preoperative visit just before surgery, postoperative day 1, week 3 (POW3), week 5, and month 2 (POM2). The main outcome measures were VA, IOP, number of glaucoma medications, and complications at all postoperative time points. Results: There was no difference in logMAR VA between the 2 groups at any time point. At POW3, IOP was significantly lower in the wick group (14.6±7.7 vs. 18.1±8.7 mm Hg, P =0.03). Number of glaucoma medications used was significantly reduced in the wick group at POW3 (0.5±0.9 vs. 1.0±1.2, P =0.02) and POM2 (0.7±1.0 vs. 1.4±1.3, P =0.02). There was no significant increase in the overall rate of complications in the wick group, but there was a higher rate of transient hyphema (28% vs. 8%, P =0.02). Conclusions: The use of 2 nylon wicks with fenestrations in nonvalved aqueous shunt device implantation can significantly lower IOP and medication burden while awaiting the dissolution of the ligature suture. Abstract : Supplemental Digital Content is available in the text.